Hyperemesis Gravidarum in First-Trimester Pregnant Saudi Women: Is Helicobacter pylori a Risk Factor? - Hussein, Khulood S. (Frontiers in Physiology, 2020)
Introduction Hyperemesis gravidarum (HG) is a serious complication of pregnancy involving nausea and vomiting which affects all facets of the lives of many women. Helicobacter pylori (H. pylori) infection has been linked to HG in some regions of the world. However, the prevalence of H. pylori in Saudi Arabian pregnant women and its link to HG has not been the subject of previous research. Detecting and treating H. pylori infection in women early in their pregnancies may lower the likelihood of adverse maternal outcomes. This study aims to assess the connection between the pathogenesis of hyperemesis gravidarum (HG) and Helicobacter pylori (H. pylori) infection in this population. Methods Forty-five pregnant women with HG were recruited from the outpatient clinic for antenatal care in the Gynecology & Obstetrics department at King Abdulaziz University Hospital. Forty-five normal pregnant women were matched as controls. Both groups underwent testing for the H. pylori antigen (HpSA) in stool samples. Results A statistically significant difference (P<0.05) was observed between the cases and controls in terms of the occurrence of H. pylori. Thirty-eight women in the HG group (84.4%) tested positive for H. pylori, while the same was true of only twenty of the controls (44.4%). The mean level of blood hemoglobin in positive cases was significantly lower than that in negative cases (9.56 ± 1.29 gm/dL vs. 11.90 ± 1.18 gm/dL, P=0.012). Conclusion H. pylori may play a contributing role in the presence of HG in the study population. It may be included with other investigations of HG, especially with cases that do not respond to conventional management and continue into the second trimester. Women with H. pylori were also more likely to suffer from anemia compared to those without the infection. For this reason, those working with pregnant women should pay close attention to those infected with H. pylori. Additional large case-control studies are necessary to better understand the part H. pylori plays and the pathogenesis of HG.